2018
DOI: 10.1136/jech-2018-211160
|View full text |Cite
|
Sign up to set email alerts
|

Consumer credit, chronic disease and risk behaviours

Abstract: BackgroundCredit scores have been identified as a marker of disease burden. This study investigated credit scores’ association with chronic diseases and health behaviours that are associated with chronic diseases.MethodsThis cross-sectional analysis included data on 2083 residents of Philadelphia, Pennsylvania, USA in 2015. Nine-digit ZIP code level FICO credit scores were appended to individual self-reported chronic diseases (obesity, diabetes, hypertension) and related health behaviours (smoking, exercise, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Estimates from low and middle-income countries (LMIC) and high-income countries indicate that between 2–3% of national health care expenditures are attributable to physical inactivity [ 37 ]. In addition, ST also appears costly, as Heron et al, (2019) estimated that prolonged ST (≥6 h) costs the United Kingdom £0.8 billion annually [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates from low and middle-income countries (LMIC) and high-income countries indicate that between 2–3% of national health care expenditures are attributable to physical inactivity [ 37 ]. In addition, ST also appears costly, as Heron et al, (2019) estimated that prolonged ST (≥6 h) costs the United Kingdom £0.8 billion annually [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scores ranged from 501 to 990, with higher numbers reflecting better creditworthiness. Consistent with previous studies (Dean et al, 2018a; Knapp & Dean, 2018), we rescaled the credit score into 10 categories of 50-point increments for interpretability of results. We also assessed scores in categories of subprime (≤700), near prime (701–800), and prime (VantageScore >800).…”
Section: Methodsmentioning
confidence: 99%
“…Second, depression and poor health behaviors are predictive of heart attack risk and are more common among those in debt (Drentea and Lavrakas 2000;Gathergood 2012;Turunen and Hiilamo 2014). Finally, the few studies that have examined health outcomes other than mental or general health have found links between indicators of cardiovascular diseases and debt (Dean et al 2019;Sweet 2018).…”
Section: Debt Health and Cardiovascular Diseasementioning
confidence: 99%